2005
DOI: 10.1210/en.2004-1283
|View full text |Cite
|
Sign up to set email alerts
|

Gα12/Gα13 Subunits of Heterotrimeric G Proteins Mediate Parathyroid Hormone Activation of Phospholipase D in UMR-106 Osteoblastic Cells

Abstract: PTH, a major regulator of bone remodeling and a therapeutically effective bone anabolic agent, stimulates several signaling pathways in osteoblastic cells. Our recent studies have revealed that PTH activates phospholipase D (PLD) -mediated phospholipid hydrolysis through a RhoA-dependent mechanism in osteoblastic cells, raising the question of the upstream link to the PTH receptor. In the current study, we investigated the role of heterotrimeric G proteins in mediating PTH-stimulated PLD activity in UMR-106 os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 34 publications
5
72
0
Order By: Relevance
“…Because PTH treatment has a positive effect on osteoblast surface in G s ␣-deficient mice, it is likely that PTH also stimulates signaling pathways downstream of PTH1R independent of G s ␣. These may include pathways activated by other PTH1R-coupled G proteins including G q /G 11 and G 12 /G 13 (29,30). We found that although intermittent PTH in older mice did not significantly increase trabecular bone volume in long bones of either WT or D/D mice within the time frame of this experiment it did significantly increase almost all parameters of bone formation in both WT and D/D mice.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Because PTH treatment has a positive effect on osteoblast surface in G s ␣-deficient mice, it is likely that PTH also stimulates signaling pathways downstream of PTH1R independent of G s ␣. These may include pathways activated by other PTH1R-coupled G proteins including G q /G 11 and G 12 /G 13 (29,30). We found that although intermittent PTH in older mice did not significantly increase trabecular bone volume in long bones of either WT or D/D mice within the time frame of this experiment it did significantly increase almost all parameters of bone formation in both WT and D/D mice.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, constitutive activation of G s -dependent signaling by an engineered G scoupled receptor also significantly increases trabecular bone mass (28). In addition to G s , PTH1R couples to several other G proteins, activating phospholipase C␤ via G q /G 11 to stimulate protein kinase C and G 12 /G 13 to stimulate phospholipase D (29,30). We have previously reported that phospholipase C (PLC) signaling via PTH1R is essential for stromal cell response to PTH in growing mice (31).…”
mentioning
confidence: 99%
“…The PPR is a member of the B subfamily of G proteincoupled receptors that can activate multiple G proteins (38,44): Gs, which activates the adenylyl cyclase/protein kinase A (PKA) pathway; the Gq/G11 family, which activates the phos-pholipase C/protein kinase C pathway; Gi, which inhibits adenylyl cyclase and exerts other actions as well; and G12/G13 (41). Through the activation of these pathways, PPR generates multiple intracellular secondary messengers, including cyclic AMP (cAMP), inositol triphosphate, diacylglycerol, and cytosolic Ca 2ϩ , which then mediate various cellular responses.…”
mentioning
confidence: 99%
“…After ligand coupling, PTHR1 activates four different intracellular signalling cascades: a) GαS-adenylyl cyclise-cAMP-protein kinase A (PKA), b) Gαq-phospholipase C (PLC) β-inositol triphosphate-cytoplasmic Ca 2+ -protein kinase C, 18 c) Gα12/13-hospholipase D-transforming protein RhoA 19 and d) β-arrestin-xtracellular signal-regulated kinase 1/2 (ERK1/2) (Figure 1). 20,21 In the skeleton, PTHR1 is expressed on the surface of osteoblasts and osteocytes.…”
Section: Activation Of Intracellular Molecular Pathwaysmentioning
confidence: 99%